The Female of Bertrana Hieroglyphica Petrunkevitch (Araneae, Argiopidae) - Arthur M. Chickering (Psyche: A Journal of Entomology)
Four species of this very interesting genus are known at the present time. Keyserling (1884) established the genus and described the first known species from a group of females from Peras, Brazil. Two other species have been described from South America by Simon (1893); one of these was from Peru and the other from Para, Brazil. Dr. Petrunkevitch was the first to describe a male which was the only specimen in the genus collected at the Wilcox camp on the San Lorenzo River. I now have about five dozen specimens from various parts of Panama and the Canal Zone with both sexes well represented. I have thought it worth while to publish a description of the female with very brief attention paid to the male.